A new environmental-based tool to support forest breeders in selecting species adapted to current and near-term climate conditions - Ricardo Cavalheiro; Aurelio Mendes Aguiar; Ranga Raju Vatsavai; Mragisha Jain; William M. Hammond; Gary Hodge; Juan Jose Acosta; Roberto Fritsche-Neto (Tree Genetics & Genomes, 2026)
This study presents SST (Species Selection Tool), a climate-based framework designed to support species selection across geographic regions and climate scenarios. The tool was developed to enable breeders to examine species selection scenarios across countries and climate horizons. Beyond identifying promising species for testing, SST prioritizes candidate species, highlights opportunities for germplasm exchange, anticipates climate-driven shifts, and maps environmental clusters and adapted genetic resources to guide near- and long-term breeding strategies. Built with the Shiny framework in R, SST allows users to upload tabular data in CSV format for flexible analyses. We demonstrate its application for a Eucalyptus breeding example in Brazil, using occurrence data from GBIF and environmental covariates from TerraClimate and CHIRPS, and complemented by CMIP6 future climate projections. Temperature and precipitation data were used to compute 19 bioclimatic variables (BIO1–BIO19) for macroenvironmental classification and species suitability assessment. SST integrates five analytical indices, scaled from 0 to 1, producing an overall suitability index and ranking species accordingly. The tool identified E. urophylla , E. brassiana , E. deglupta , and E. pellita as the most suitable for the study area in the Maranhão State, Brazil. Open-source and user-friendly, SST accelerates breeding decisions, supports climate-adaptive planning, and provides access to advanced analytical tools. The tool is a useful contribution to forest management and forest tree breeding, supporting data-driven strategies for sustainable forestry under changing climates.

Regulation of chemicals demands assessment of risks rather than identification of hazards only - P. Marx-Stoelting; V. Ritz; M. Herzler; C. Kneuer; K. Aiello-Holden; S Brescia; S. E. Escher; S. Feustel; E. Fritsche; J. Gebel; E. F. Kenny; R. Landsiedel; et al. (Archives of Toxicology, 2026)
This position paper was collaboratively written during the international expert symposium “EU Chemicals Assessment - Risk- or Hazard-based?” that was organised by the German Federal Institute for Risk Assessment (BfR) in Berlin on November 27th and 28th 2025. Twenty experts from several institutions and European countries considered the scientific merits of both hazard-based and risk-based approaches to chemical safety assessment. While hazard information is essential, it does not reflect real-world exposure conditions that determine the likelihood of harm. On balance, we support a risk-based approach because it enables more proportionate, transparent and scientifically grounded regulatory decisions.

P18-67 Regulation of key neurodevelopmental processes by disease pathways and nuclear receptors in a human Neurosphere Assay - E. Kuchovska; K. Koch; K. Bartmann; K. Schluppmann; A. Donmez; J. Klose; G. Raad; M. Schade; L.-C. Saborowski; E. Fritsche (Toxicology Letters, 2025)

P18-65 Advancing the Grouping and Harmonization of Similar Key Events in the AOP Wiki: Ontology-Based Key Event Component Combinations as Catalysts for Integration - J. Filipovska; K. Audouze; J. Blum; L.-A. Clerbaux; E. Coerek; E. Demuynck; S. Edwards; E. Fritsche; L. Gerner; K. Groh; G. Hench; N. Jeliazkova; et al. (Toxicology Letters, 2025)

P14-15 Species-, Cell Type- and Developmental-Specific Variability in DNA Repair Capacities of Human and Rodent Neural Progenitor Cells - L.P. Czernik; M. Pahl; L. Dittmann; E.R. de Caro; L.M. Stark; E. Fritsche; J. Tigges; K. Koch (Toxicology Letters, 2025)

P05-45 Ontology maps: data integration tools for applications in toxicology - B. Staumont; L. Ladeira; A. Gamba; A. Verhoeven; J. Sanz Serrano; E. Kuchovska; J. Berkhout; D. A.; M. Teunis; T.H. Luechtefeld; T. Hartung; R. Jover; et al. (Toxicology Letters, 2024)

OS02-03 Using a systems biology approach to construct adverse outcome pathway networks aligned with the FAIR principles - L. Ladeira; A. Mazein; M. Ostaszewski; A. Verhoeven; E. Kuchovská; J. Sanz-Serrano; A. Drees; K. Reiche; K. Sewald; E. Fritsche; M. Vinken; L. Geris; et al. (Toxicology Letters, 2024)

S05-01 Functional mapping of neurodevelopmental disorders to ontology-based DNT NAMs for Next Generation Risk Assessment of chemicals - E. Kuchovska; L. Ladeira; K. Bartmann; D. Polozij; N. Gorts; E. Corek; A. Donmez; L.-C. Saborowski; F. Bendt; M. Schade; G. Raad; A. Gamba; et al. (Toxicology Letters, 2024)

P22-35: Mapping of DNT NAMs’ signaling pathways in human physiology and disease for regulatory application - E. Kuchovska; K. Bartmann; L. C. Maia Ladeira; A. Dönmez; L.-C. Saborowski; F. Bendt; M. Schade; G. Raad; R. Lesage; A. Gamba; B. Staumont; L. Geris; et al. (Toxicology Letters, 2023)

P21-14: Neurodevelopmental toxicity of T-2 mycotoxin in human-based primary and induced pluripotent stem cell-derived neural progenitor cells in 3D and 2D - M. Taroncher Ruiz; J. Kapr; K. Bartmann; J. Tigges; Y. Rodriguez-Carrasco; M.J. Ruiz; E. Fritsche (Toxicology Letters, 2023)

P16-40: Metabolic effects and half-life of organophosphate and pyrethroid pesticides and their metabolites in HepaRG cells - K. Fritsche; D. Lichtenstein; C. Muñoz; M. Garí; K. Abass; J.O. Grimalt; A. Braeuning (Toxicology Letters, 2023)

OS03-02: Comparative analysis of human and rat neural stem-/progenitor cell functions during developmental time-dependent genotoxin exposure in vitro - M. Pahl; J. Klose; E. Fritsche (Toxicology Letters, 2023)

Establishment of a human cell-based in vitro battery to assess developmental neurotoxicity hazard of chemicals - Jonathan Blum; Stefan Masjosthusmann; Kristina Bartmann; Farina Bendt; Xenia Dolde; Arif Dönmez; Nils Förster; Anna-Katharina Holzer; Ulrike Hübenthal; Hagen Eike Keßel; Sadiye Kilic; Jördis Klose; et al. (Chemosphere, 2023)

Correction to: Female reproductive organs of Brassica napus are more sensitive than male to transient heat stress - Sheng Chen; Renu Saradadevi; Miriam S. Vidotti; Roberto Fritsche-Neto; Jose Crossa; Kadambot H. M. Siddique; Wallace A. Cowling (Euphytica, 2021)

Female reproductive organs of Brassica napus are more sensitive than male to transient heat stress - Sheng Chen; Renu Saradadevi; Miriam S. Vidotti; Roberto Fritsche-Neto; Jose Crossa; Kadambot H. M. Siddique; Wallace A. Cowling (Euphytica, 2021)
Oilseed rape ( Brassica napus L.) is sensitive to heat stress during the reproductive stage, but it is not clear whether the male and female reproductive organs differ in their sensitivity to heat stress. In this study, full diallel crossing experiments were conducted among four genotypes of B. napus under control, moderate and high heat stress conditions for five days immediately before and two days after crossing. General combining ability (GCA), specific combining ability (SCA) and reciprocal effects were analyzed to evaluate the genetic basis of heat stress tolerance in male and female reproductive organs. High female temperature (Tf) and high male temperature (Tm) reduced the number of fertile pods and seeds set per floret, and the significant Tf × Tm interaction indicated that female reproductive organs were more sensitive to heat stress than male reproductive organs. There were no overall GCA, SCA or reciprocal effects across all combinations of Tf and Tm. However, a significant reciprocal × Tf effect was found, suggesting that genotypes differed in their ability to set fertile pods and seeds as Tf increased. The relative heat tolerance of G1 as a female increased as Tf increased, and the relative heat tolerance of G2 as a male decreased as Tf increased. In summary, reciprocal diallel crossing has demonstrated that female reproductive organs of B. napus are more sensitive than male to transient heat stress at the early flowering stage, and genotypes differ in relative heat tolerance in the male and female reproductive organs as Tf increases.

Serendipita restingae sp. nov. (Sebacinales): an orchid mycorrhizal agaricomycete with wide host range - Yohan Fritsche; Morgana E. Lopes; Marc-André Selosse; Valdir M. Stefenon; Miguel P. Guerra (Mycorrhiza, 2021)

Minimum Selenium Requirements Increase When Repleting Second-Generation Selenium-Deficient Rats but Are Not Further Altered by Vitamin E Deficiency - Roger A. Sunde; Kevin M. Thompson; Kevin L. Fritsche; Jacqueline K. Evenson (Biological Trace Element Research, 2017)

Estimation of satellite antenna phase center offsets for Galileo - P. Steigenberger; M. Fritsche; R. Dach; R. Schmid; O. Montenbruck; M. Uhlemann; L. Prange (Journal of Geodesy, 2016)

International STakeholder NETwork (ISTNET): creating a developmental neurotoxicity (DNT) testing road map for regulatory purposes - Anna Bal-Price; Kevin M. Crofton; Marcel Leist; Sandra Allen; Michael Arand; Timo Buetler; Nathalie Delrue; Rex E. FitzGerald; Thomas Hartung; Tuula Heinonen; Helena Hogberg; Susanne Hougaard Bennekou; et al. (Archives of Toxicology, 2015)

Assessing the Current Evolution of the Greenland Ice Sheet by Means of Satellite and Ground-Based Observations - A. Groh; H. Ewert; M. Fritsche; A. Rülke; R. Rosenau; M. Scheinert; R. Dietrich (Surveys in Geophysics, 2014)

BDE-47 and 6-OH-BDE-47 modulate calcium homeostasis in primary fetal human neural progenitor cells via ryanodine receptor-independent mechanisms - Kathrin Gassmann; Timm Schreiber; Milou M. L. Dingemans; Guido Krause; Claudia Roderigo; Susanne Giersiefer; Janette Schuwald; Michaela Moors; Klaus Unfried; Åke Bergman; Remco H. S. Westerink; Christine R. Rose; et al. (Archives of Toxicology, 2014)

Reducing the draconitic errors in GNSS geodetic products - C. J. Rodriguez-Solano; U. Hugentobler; P. Steigenberger; M. Bloßfeld; M. Fritsche (Journal of Geodesy, 2014)

Biosynthetic genes and activity spectrum of antifungal polyynes from C ollimonas fungivorans T er331 - Kathrin Fritsche; Marlies van den Berg; Wietse de Boer; Teris A. van Beek; Jos M. Raaijmakers; Johannes A. van Veen; Johan H. J. Leveau (Environmental Microbiology, 2014)
Summary The antifungal activity of bacteria from the genus C ollimonas has been well documented, but the chemistry and gene functions that underlie this phenotype are still poorly understood. Screening of a random plasposon insertion library of C ollimonas fungivorans T er331 for loss‐of‐function mutants revealed the importance of gene cluster K , which is annotated to code for the biosynthesis of a secondary metabolite and which features genes for fatty acid desaturases and polyketide synthases. Mutants in gene cluster K had lost the ability to inhibit hyphal growth of the fungus A spergillus niger and were no longer able to produce and secrete several metabolites that after extraction and partial purification from wildtype strain T er331 were shown to share a putative ene‐triyne moiety. Some but not all of these metabolites were able to inhibit growth of A . niger , indicating functional variation within this group of C ollimonas ‐produced polyyne‐like ‘collimomycins’. Polymerase chain reaction analysis of isolates representing different C ollimonas species indicated that the possession of cluster K genes correlated positively with antifungal ability, further strengthening the notion that this cluster is involved in collimomycin production. We discuss our findings in the context of other bacterially produced polyynes and the potential use of collimomycins for the control of harmful fungi.

Low-degree earth deformation from reprocessed GPS observations - Mathias Fritsche; R. Dietrich; A. Rülke; M. Rothacher; P. Steigenberger (GPS Solutions, 2010)

A prevalent POLG CAG microsatellite length allele in humans and African great apes - Anja T. Rovio; Josef Abel; Arja L. Ahola; Aida M. Andres; Jaume Bertranpetit; Antoine Blancher; Ronald E. Bontrop; Leona G. Chemnick; Howard J. Cooke; James M. Cummins; Heidi A. Davis; David J. Elliott; et al. (Mammalian Genome, 2004)

Cloning of Baeyer‐Villiger monooxygenases from Comamonas , Xanthobacter and Rhodococcus using polymerase chain reaction with highly degenerate primers - Jan B. Van Beilen; Frédéric Mourlane; Markus A. Seeger; Jasminka Kovac; Zhi Li; Theo H. M. Smits; Urban Fritsche; Bernard Witholt (Environmental Microbiology, 2003)
Summary To clone novel type 1 Baeyer‐Villiger monooxygenase (BVMO) genes, we isolated or collected 25 bacterial strains able to grow on alicyclic compounds. Twelve of the bacterial strains yielded polymerase chain reaction (PCR) fragments with highly degenerate primers based on the sequences of known and putative BVMOs. All these fragments were found to encode peptides homologous to published BVMO sequences. The complete BVMO genes and flanking DNA were cloned from a Comamonas , a Xanthobacter and a Rhodococcus strain using the PCR fragments as probes. BVMO genes cloned from the first two strains could be expressed to high levels in Escherichia coli using standard expression vectors, and the recombinants converted cyclopentanone and cyclohexanone to the corresponding lactones. The Rhodococcus BVMO, a putative steroid monooxygenase, could be expressed after modification of the N‐terminal sequence. However, recombinants expressing this protein did not show activity towards progesterone. An esterase homologue located directly upstream of the Xanthobacter BVMO gene and a dehydrogenase homologue encoded directly downstream of the Comamonas sp. NCIMB 9872 BVMO gene were also expressed in E. coli and shown to specify lactone hydrolase and cyclohexanol dehydrogenase activity respectively.

Maximum rates of N 2 fixation and primary production are out of phase in a developing cyanobacterial bloom in the Baltic Sea - J. R. Gallon; A. M. Evans; D. A. Jones; P. Albertano; R. Congestri; B. Bergman; K. Gundersen; K. M. Orcutt; K. von Bröckel; P. Fritsche; M. Meyerhöfer; K. Nachtigall; et al. (Limnology and Oceanography, 2002)
Although N 2 ‐fixing cyanobacteria contribute significantly to oceanic sequestration of atmospheric CO 2 , little is known about how N 2 fixation and carbon fixation (primary production) interact in natural populations of marine cyanobacteria. In a developing cyanobacterial bloom in the Baltic Sea, rates of N 2 fixation (acetylene reduction) showed both diurnal and longer‐term fluctuations. The latter reflected fluctuations in the nitrogen status of the cyanobacterial population and could be correlated with variations in the ratio of acetylene reduced to 15 N 2 assimilated. The value of this ratio may provide useful information about the release of newly fixed nitrogen by a cyanobacterial population. However, although the diurnal fluctuations in N 2 fixation broadly paralleled diurnal fluctuations in carbon fixation, the longer‐term fluctuations in these two processes were out of phase.

Mineralization of 2-amino-4,6-dinitrotoluene by manganese peroxidase of the white-rot fungus Nematoloma frowardii - K. Scheibner; M. Hofrichter; W. Fritsche (Biotechnology Letters, 1997)